Knowledge and Attitude of Senior High School Students toward Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome - Reswari, Arnova; Mutyara, Kusmandewi; Lidyana, Lynna (Althea Medical Journal, 2016)
Background: Indonesia has experienced more than 25% rise of Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) incidence. One of the provinces mostly affected is West Java. Proper knowledge of HIV/AIDS can develop attitude and practice to prevent the spread of HIV/AIDS, and in effect, its incidence. This study was conducted to describe the knowledge and attitude of Senior High School (Sekolah Menengah Atas, SMA) students toward HIV/AIDS.Methods: This descriptive study was conducted using a cross-sectional method and used secondary data with total sampling technique, from Jatinangor Cohort Research Team of the Faculty of Medicine, Universitas Padjadjaran. The samples were obtained by stratified cluster random sampling. Two hundred and seventy seven studentsâ knowledge and attitude were assessed in Senior High School in Jatinangor, on May 2013Results: Senior High School students in Jatinangor mostly (50.2%) had a poor level of knowledge, yet 51.3% positive attitude toward HIV/AIDS. There were still misconception regarding transmission media of HIV/AIDS and mode of transmission HIV/AIDS. Information source on HIV/AIDS were teachers (96.4%), followed by television (93.5%), internet (86.6%), friends (84.8%), health workers (69.7%), newspapers (62.1%), parents (61%), magazines (55.2%), and radio (33.2%).Conclusions: Although most of the Senior High School students in Jatinangor have a poor level of knowledge, they have a positive attitude toward HIV/AIDS. The main information source on HIV/AIDS is teacher. [AMJ.2016;3(1):73â8]Â DOI:Â 10.15850/amj.v3n1.712